Diverse Insights Revealing Nuances of the Culture-High Ability Nexus: An Interdisciplinary Search - Ambrose, Don; Ambrose, Valerie K. (International Journal for Talent Development and Creativity, 2022)
Discovering the cultural dimensions of high ability is analogous to a large-scale creative problem-solving initiative. Just as the early phases of the creative-problem-solving process require broad-scope searches through diverse data sources, understanding the culture-giftedness nexus requires broad-scope excursions through interdisciplinary scholarly sources that can enable deeper understanding of culture. Here, we engage in such an excursion and borrow insights from leading thinkers in cultural anthropology, English studies, political science, ethical philosophy, and history, and use these insights to generate new ways of thinking about the cultural aspects of giftedness. The foreign concepts analyzed include anti-anti-relativism, mythological archetypes, the artificial reification of culture, distant proximities that influence personal identity, ethnocentrism and particularist morality, differing views of nature, and the influence of critical communities and motley coalitions in a globalized world.